Urbanização e novas relações cidade-campo: os processos com a criação do estado do Tocantins e de sua capital Palmas na Amazônia Oriental - Kelly Bessa (Confins)
The founding of Tocantins state, its inclusion in Brazil’s North Region (more specifically, within Eastern Amazon), and the implementation of its capital city, Palmas, in 1989, were major factors of urbanization in the area, both with regard to urban space (particularly that of Palmas) and urban network, which became spearheaded by Palmas. This city has not developed from spontaneous social and spatial practices but, rather, from deliberate actions on the part of the first state government, which decided to implement a city with the purpose of housing the state’s political and administrative apparatus. Within this scenario, new city-countryside relations have evolved from the conflictive expropriation of rural lands which, once incorporated into the urban space, are generally viewed as merchandise due to the actions of state administrators. Other agents have gradually acquired and reserved lands for speculation; these include rural landowners, who transfer capital generated in the countryside, and construction companies and real estate developers and promoters, who extend the transference of regional capital to other sectors of the urban economy. A transference of people from the countryside and other cities has also ensued, the result of a pull factor on the regional population. More recently, agribusiness has triggered new relations among urban, rural, and regional spaces, fostering enormous investment within the real estate sector and other segments of the urban economy. These are all mechanisms that aim to accumulate capital, whether in the real estate sector or in the urban functional structure, hence attracting surpluses from the countryside and the wider region. These surpluses have changed the original urban plan and urban network standards, consequently revealing new city-countryside relations and urban-rural-regional processes which call for more rigorous analyses. Addressing such issues is this study’s central aim.